Trichoderma viride: An Eco-Friendly Biocontrol Solution Against Soil-Borne Pathogens in Vegetables Under Different Soil Conditions - Shomaila Iqbal; Muhammad Ashfaq; Muhammad Junaid Rao; Khalid Saifullah Khan; Amir Humayun Malik; Mirza Abid Mehmood; Muhammad Sarmad Fawaz; Aqleem Abbas; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Abdulwahed Fahad Alrefaei; Mingzheng Duan (Horticulturae)
The use of biological methods to control plant diseases has garnered attention due to their eco-friendly and economically viable nature. Trichoderma spp. are the most ubiquitous fungal saprophytes that can often grow as opportunistic symbionts, are eco-friendly, and are not reported to exert any environmental hazard. Soil-borne pathogens can significantly impact the yield of chilli and tomato crops. The study was conducted to explore the impact of various salts (NaCl, MgCl2, CaCl2, and KCl) and their concentrations (1%, 5%, 10%, and 15%) on the mycelial growth and sporulation of Trichoderma viride followed by its mass multiplication on diverse organic substrates like wheat seeds, wheat husks, mungbean seeds, maize seeds, rice seeds, pea seeds, sorghum seeds, banana peel, apple peel, pomegranate peel, citrus peel, tomato waste, chilli waste, spinach waste, cabbage waste, potato peel, onion peel, cucumber peel, carrot peel, used black tea leaves, used green tea leaves, poultry waste, and cow and goat dung. The study assessed the biocontrol potential of Trichoderma viride against important soil-borne pathogens in chilli (Pythium aphanidermatum, Phytophthora capsici, and Fusarium oxysporum) and tomato (Pythium aphanidermatum, Phytophthora infestans, and F. oxysporum) cropping in the pot and field experiments using saline and alkaline soils. Seed treatment with T. viride significantly enhanced the germination rates of both chilli and tomato crops, with sorghum being the most conducive substrate for mass-multiplying T. viride. The results revealed that lower salt concentrations minimally affected T. viride growth, while higher concentrations hampered both growth and sporulation. Optimal disease control and plant height were observed at a 20 mg concentration of T. viride, consequently applied in vivo using various application methods, i.e., seed treatment, root dip, irrigation, and mixed treatments (all the methods like seed treatment, root dip method, and irrigation method applied together) to manage soil-borne pathogens. Particularly, T. viride application through irrigation and mixed treatments demonstrated strong efficacy. These findings underscore the potential of T. viride application in saline and alkaline soils to manage soil-borne pathogens like Pythium, Phytophthora spp., and Fusarium spp. This study lays the foundation for the practical application of biocontrol agents, like T. viride, in Pakistani agricultural conditions. Moreover, there is a need for further exploration into the genetic mechanisms involved in disease inhibition and plant growth promotion, along with understanding the impact of T. viride on the metabolic pathways of host plants.